Պայքարի նոր փուլ Պաղեստինի համար - Կարապետյան, Ռուբեն («Զանգակ - 97»)
Since the creation of the State of Israel in 1948 the Palestinian problem has become the core of the Arab-Israeli eonfliet. Düring almost the half Century of wars, hatred and bloodsed between the Arabs and Israel the problem of Palestine is still remained unresolved. The peaee process initiated at the beginning of 90՝s has brought some practica! results together with the hope that eventually the Palestinian State will be established alongside with Israel.
Keywords: Պատմություն